(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
Information literacy is a critical skill in today's knowledge-driven world, and its significance is magnified in the context of sustainable development. This paper explores the information literacy towards Sustainable Development Goals (SDGs) in Nigeria. Information literacy empowers individuals to access, evaluate, and utilize information effectively, which is pivotal for making informed decisions and fostering sustainable development. In Nigeria, a country with diverse challenges and opportunities, information literacy plays a central role in addressing the complex issues outlined in the SDGs. As Nigeria strives to achieve the SDGs, information literacy must be integrated into national development strategies. Enhancing information literacy skills across all sectors of society will empower individuals to make informed decisions, contribute to economic growth, and participate meaningfully in the democratic process. Furthermore, information literacy is a key driver for innovation, entrepreneurship, and sustainable development, aligning with the broader global goals of leaving no one behind and creating a more just, equitable, and sustainable world. It was highly recommended that, government should collaborate with educational authorities to integrate information literacy into the national curriculum from primary to tertiary levels. Government should provide training and professional development opportunities for educators to enhance their own information literacy skills and teaching methods. They should equip teachers with resources and tools to incorporate information literacy into their classrooms effectively.